2018
DOI: 10.1186/s13006-018-0190-9
|View full text |Cite
|
Sign up to set email alerts
|

Higher likelihood of 6-months exclusive breastfeeding among HIV infected than uninfected mothers: a household survey in Kenya

Abstract: BackgroundExclusive breastfeeding (EBF) (breast milk feeding without additional food or drink, except medicine) is associated with deceased risk of postnatal transmission of HIV from mother to child.MethodsThis analysis used data from a household survey in Western Kenya in 2011. Participants were mothers with HIV and uninfected mothers, aged ≥14 years who gave birth in the prior year (ever breastfed) within the Kenya Medical Research Institute/US Centers for Disease Control and Prevention (KEMRI/CDC) Health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…is study result agreed with Kenya [27]. e polygamous marriage is commonly practiced in the study area and may favor a child to undernutrition and stunting among under-five children.…”
Section: Discussionsupporting
confidence: 83%
“…is study result agreed with Kenya [27]. e polygamous marriage is commonly practiced in the study area and may favor a child to undernutrition and stunting among under-five children.…”
Section: Discussionsupporting
confidence: 83%
“…Being HIV-positive resulted in two facilitators: it gave women access to extensive health services including the program intervention in the parent trial (intensive EBF counseling), and it motivated women to avoid HIV transmission to infants,which was not the case for HIV-positive women. This has also been seen in other studies conducted in Kenya and reporting that EBF is more common among HIV-positive women compared to HIV-negative women (Oiye et al 2017;Okanda et al 2018). Previous studies have reported that male attendance to clinic improves infant HIV-free survival (Aluisio et al 2016;Alusio et al 2011).…”
Section: Discussionsupporting
confidence: 60%
“…This finding is supported by similar study previously done in Kenya. 24 A more likely explanation might be most women are economically dependent on their husbands and cannot afford the cost of well-nourished and dietary diversity unless they get support from their husbands. In addition, the husband could be so busy to contribute equally to his wives.…”
Section: Discussionmentioning
confidence: 99%